A Review of Consideration of Ethnic Factors During Drug Approval Process - SudershanGoud Gokari (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Purpose To determine feasibility of drug registration for the selected drugs at USFDA based on the ICH E5 guideline. Methods Methodology involves two steps, they are 1. Determination of ethnic sensitivity of the selected drugs based on factors such as pharmacokinetics (PK), pharmacodynamic (PD), therapeutic range, and metabolism etc., given in appendix D of ICH E5 guidelines. 2. Determination of the need for the bridging studies after determining ethnic sensitivity of the selected drugs based on the ICH E5 guidelines. Results After the extensive analysis of the selected drugs, ethnic factors found to have profound effect across all classes of drugs like Analgesics and Anti-Inflammatory Agents, Central Nervous System Agents, Antihypertensive Drugs, Anticoagulants, Metabolism and Endocrine Agents, Immunomodulators, Anticancer Agents, Gastrointestinal Agents, Antiparasitic Agents and Genitourinary Agents. Conclusion Some drugs may be ethnically insensitive and some other drugs may be ethnically sensitive among the selected drugs based on the ICH E5 guideline. Drugs which are ethnically insensitive may be approved by USFDA (United States Food and Drug Administration) without need of bridging studies where as drugs which are ethnically sensitive and they need bridging studies before they can be approved.